(3GdJLGQI YHQ GdMGShH (B:s (3eGgjJgG, EKHGJgG, hSGFd MeGjJgG, GdbGfhf GdhGLH GdJWHjb YdjgG aj cd ef GdCQOf heUQ hEeGQI OHj (B: (3OQGSI ebGQfI (B/s - (3GdcShGfj, YGeQ eMehOs ((3YeGf, GdCQOf (B:s (3OGQ GdKbGaI ddfTQ hGdJhRjY,s, 2009)
(3JCJj gPg GdOQGSI hGdJj YfhGfgG HGdJLGQI YHQ GdMGShH hde JYfhf HGdeYGedGJ YHQ GdMGShH ddHjGf hGdJhVjM hGdJCcjO Ydi CgejI GdJLGQI GdJj JJe YHQ GdMGShH aj hbJfG GdMGVQ hGdJj bO dG fHGdZ EPG bdfG EfgG GSJhYHJ cGaI CTcGd GdJYGedGJ GdCNQi GdJj JJe YHQ GdMGShH ef NdGd GdJUOj dJYQjagG hef Ke HjGf CMcGegG hJMOjO WQb EKHGJ eNQLGJgG hGdJYQa Ydi hSGFd MeGjI eeGQSJgG ShGA ef GdfGMjI GdLRGFjI Ch GdeOfjI hCNjQG JMOjO GdbGfhf GdhGLH GdJWHjb YdjgG(B. (3hbHd Cf fTQY aj OQGSJfG gPg dG HO ef GdJegjO hdh HEjLGR dehVhY GdJLGQI GdEdcJQhfjI afJYQa Ydi cjajI fTCJgG hBdjI YedgG hOhQgG hhXjaJgG hCgejJgG Ydi GdUYjO GdGbJUGOj, eSJYQVG GdehVhYGJ GdJGdjI (B: (3JbOje hJbSje, GdaUd GdJegjOj (B: (3fXQI YGeI Ydi GdJLGQI GdEdcJQhfjI, GdaUd GdChd (B: (3eGgjI GdJLGQI YHQ GdMGShH, GdaUd GdKGfj (B: (3WQb EKHGJ GdJLGQI GdEdcJQhfjI, GdaUd GdKGdK (B: (3MeGjI GdJLGQI YHQ GdMGShH, GdaUd GdQGHY (B:(3G dbGfhf GdhGLH GdJWHjb Ydi GdJLGQI YHQ GdMGShH(B.s
(3HHdjhLQGajI (B: (3UaMI (B293-304.s
Keywords: (3GdJLGQI GdEdcJQhfjIs -- (3bhGfjf hJTQjYGJs; (3GdJLGQI GdEdcJQhfjIs -- (3bhGfjf hJTQjYGJs -- (3GdCQOfs; (3GdJLGQI GdEdcJQhfjIs -- (3bhGfjf hJTQjYGJs -- (3eUQs; (3GdJLGQI GdEdcJQhfjIs -- (3bhGfjf hJTQjYGJs -- (3GdEeGQGJ GdYQHjI GdeJMOIs -- (3OHjs